一种用于评估空腹血糖受损和2型糖尿病患病风险的整合生物标志物体系 (2021)
本发明公开了一种用于评估空腹血糖受损(IFG)和2型糖尿病(T2DM)患病风险的整合生物标志物体系，所述整合生物标志物体系包括样本中L-谷氨酰胺、L-缬氨酸、L-亮氨酸、L-赖氨酸、L-脯氨酸、L-苯丙氨酸、L-精氨酸、L-谷氨酸、L-异亮氨酸、L-蛋氨酸、左旋肉碱、乙酰基左旋肉碱、溶血磷脂酰胆碱(LPC(P-16:0))、LPC(17:0)、LPC(14:0)、丙酰基左旋肉碱的定量测定结果。本发明首次公开了用于IFG和T2DM评估的整合生物标志物体系。本发明建立的IFG和T2DM受试者血清样本整合生物标志物体系包含了相互关联的生物网络路径上的生物标志物组，反映了IFG和T2DM的整体代谢特征信息，规避了单一或孤立地分析生物标志物而缺乏整体综合地反映疾病的特征信息。 An integrated biomarker system for evaluating a risk of impaired fasting glucose (IFG) and type 2 diabetes mellitus (T2DM) for the first time is disclosed. The integrated biomarker system includes quantitative determination results of L-glutamine, L-valine, L-leucine, L-lysine, L-proline, L-phenylalanine, L-arginine, L-glutamic acid, L-isoleucine, L-methionine, L-carnitine, acetyl-L-carnitine, lysophosphatidyl choline (LPC (P-16:0)), LPC (17:0), LPC (14:0) and propionyl-L-carnitine in a sample. The integrated biomarker system for IFG and T2DM of subject serum sample contains a correlative biomarker group on a biological network path to reflect the overall metabolic characterist